Volumetric modulated arc therapy with flattening filter free beams for isolated abdominal/pelvic lymph nodes: report of dosimetric and early clinical results in oligometastatic patients - Alongi, Filippo (BioMed Central, 2012)
BACKGROUND: SBRT is a safe and efficient strategy to locally control multiple metastatic sites. While research in the physics domain for Flattening Filter Free Beams (FFF) beams is increasing, there are few clinical data of FFF beams in clinical practice. Here we reported dosimentric and early clinical data of SBRT and FFF delivery in isolated lymph node oligometastatic patients. METHODS: Between October 2010 and March 2012, 34 patients were treated with SBRT for oligometastatic lymph node metastasis on a Varian TrueBeam(TM) treatment machine using Volumetric Modulated Arc Therapy (RapidArc). We retrospectively evaluated a total of 25 patients for isolated lymph node metastases in abdomen and/or pelvis treated with SBRT and FFF (28 treatments). Acute toxicity was recorded. Local control evaluation was scored by means of CT scan and/or PET scan. RESULTS: All dosimetric results are in line with what published for the same type of stereotactic abdominal lymph node metastases treatments and fractionation, using RapidArc. All 25 FFF SBRT patients completed the treatment. Acute gastrointestinal toxicity was minimal: one patient showed Grade 1 gastrointestinal toxicity. Three other patients presented Grade 2 toxicity. No Grade 3 or higher was recorded. All toxicities were recovered within one week. The preliminary clinical results at the median follow up of 195 days are: complete response in 12 cases, partial response in 11, stable disease in 5, with an overall response rate of 82%; no local progression was recorded. CONCLUSIONS: Data of dosimetrical findings and acute toxicity are excellent for patients treated with SBRT with VMAT using FFF beams. Preliminary clinical results showed a high rate of local control in irradiated lesion. Further data and longer follow up are needed to assess late toxicity and definitive clinical outcomes.